Dinâmica de uma comunidade arbórea após enchente em fragmentos florestais no sul de Minas Gerais - Silva, Ana Carolina da (2011)
In order to evaluate the impact of a catastrophic flooding on tree individuals, it was carried out, in 2007, evaluation of an alluvial area in São Sebastião da Bela Vista, MG, where it was sampled five alluvial fragments and a riparian forest, which was inventoried in 2005. Results show that after the flooding, a short-term dynamics was characterized by a mortality rate higher than recruitment rate and loss rate was higher than gain rate in basal area. However, the structure of the community was not affected, because frequency of surviving and dead trees in the diametric classes was proportional to the initial number of individual in each class. The results allowed to conclude that although there was no alteration in the diametric structure, the tree community dynamics reflected the disturbance caused by the flooding.